ANALISIS YURIDIS AKIBAT HUKUM TERHADAP PERUBAHAN ALAMAT KANTOR YANG TIDAK DILAPORKAN KEPADA MAJELIS PENGAWAS DAERAH - Faisal Ramadhan Harahap; Budiman Ginting; Suprayitno - (jurnal.unprimdn.ac.id, 2021)
A notary is obliged to report any changes of his registered office address to the Regional Supervisory (henceford refrered to as MPD). Pursuant to the regulations of the Minister of Law and Human Right Number 15/2020 on the procedures of inspections by supervisory council, MPD gives a notary a minimum of 1 (one) regular visit a year. This Research is encouragedby the experience service user who misses out a notary’s new office address to MPD. This Research problems are how to changes to a notary’s registered office address are regulated by the law, how legal sanctions are regulated by the law to a notary for not reporting changes to his registered office address, and what efforts are made by MPD to enforce the law against any notary who does not report changes of his registered office address. Emprirical Normative research method is employed as this research studies primary legal materials such as the Law Number 4/2014, the Regulations of Minister of Law and Human Right Number 19/2019, and the Minister of Law and Human Right Number 61/2016, as well as references and secondary materials supported with interviews with informans. The objective of this research are to investigate and to analyse the laws and to a notary for not reporting changes of his registered office address, and the efforts made by MPD to enforce the againsts any notary who does not report changes of his registered office address. The research concludes that the obligation of a notary to report changes to his registered office address is specified in Regulations of the Minister of Law and Human Right Number 19/2019 and the other notar;s obligations are stipulated in the Law on Notary Functions. The imposition of sanction such as a registered office address is obstructed by the long-winded bureaucracy causing difficulties to MPD in supervising notaries and enforcing the fulfilment of laws and regulations concerning notary’s obligations be synchronized, bureaucracy process to impose the sanction of written deterrant to notaries be steamlined, facilities and insfrastucture required by MPD to perform their duties be completed, and double functions of members of MPD be avoided that the supervision over notaris can be more optimal.